FAKTOR EKSTERNAL YANG MEMENGARUHI HASIL BELAJAR BIOLOGI KELAS XI MIPA SMA NEGERI 37 JAKARTA SAAT PANDEMI COVID-19 - Fajar Adinugraha; Andriyan Ino Ponto; Riska Septia Wahyuningtyas (STKIP NU Kabupaten Tegal, 2022)
The aims of this research include: 1) to describe the external factors of Class XI MIPA students at SMA Negeri 37 Jakarta; and 2) to analyze the relationship of students' external factors to the learning outcomes of Biology Class XI MIPA SMA Negeri 37 Jakarta. The survey method was used in this study. The questionnaire was given to 148 respondents and was declared valid. The dominant external factors in class XI MIPA SMA Negeri 37 Jakarta sequentially are family environment factors > school environmental factors = parental education environment = friends factor > community environmental factors = time factor. The value of student learning outcomes in class XI MIPA SMAN 37 is above the KKM with an average of 76.13. There is a positive relationship/correlation between external factors and Biology learning outcomes for students of class XI MIPA SMAN 37 Jakarta. The very low correlation coefficient may be caused by other external factors, including zoom fatigue, limited network/signal, and limited internet quota owned by students.